Exploring healthcare professionals' perspectives of barriers and facilitators to supporting people with severe mental illness and Type 2 diabetes mellitus. (27th November 2019) - Papachristou Nadal, Iliatha; Cliffton, Catherine; Chamley, Mark; Winkley, Kirsty; Gaughran, Fiona; Ismail, Khalida
Abstract: Individuals with comorbid severe mental illness (SMI) and diabetes experience an average mortality gap of 20 years compared to individuals without these conditions. There has been some recognition by policies that there is a gap between mental healthcare and physical healthcare for SMI patients. Despite this, there are still no defined care pathways for individuals with SMI and diabetes. The aim of this study was to explore healthcare professionals' (HCPs) perspectives of barriers and solutions to supporting people with SMI and diabetes. HCPs in areas of South London were invited to attend a workshop event to discuss their views of SMI and diabetes pathways. Fifty participants were recruited using the Local Care Network. HCPs included GPs, mental health nurses, psychiatrists, diabetologists and care co‐ordinators. The main themes were as follows: (a) poor coordination of care and care planning between services; (b) key techniques to improve integrated care; (c) perceived difficulties achieving better care and (d) supporting patient empowerment. The findings and recommendations from this workshop may provide some insight into key factors in providing and improving integrated SMI and diabetes care for patients in South East London and further afield.